Arabidopsis thaliana Cuticle Composition Contributes to Differential Defense Response to Botrytis cinerea - Aragón, Wendy; Formey, Damien; Aviles-Baltazar, Norma Yaniri; Torres, Martha; Serrano, Mario (Frontiers in Plant Science, 2021)
The chemical composition of the plant cuticle can change in response to various abiotic or biotic stresses and play essential functions in disease resistance responses. Arabidopsis thaliana mutants altered in cutin content are resistant to Botrytis cinerea, presumably due to increase cuticular water and solute permeability, allowing faster induction of defense responses. Within this context, our knowledge on wax mutants is limited against this pathogen. We tested the contribution of the cuticular components to immunity to B. cinerea by using mutants altered in either cutin or wax alone, or in both cutin and wax content. We found that even all tested mutants showed an increased permeability and ROS accumulation in comparison to wild-type plants, only cutin mutants showed resistance. To elucidate the early molecular mechanisms underlying cuticle-related immunity, we performed a transcriptomic analysis. A set of upregulated genes involved in the cell wall integrity and accumulation of ROS were shared by cutin mutants bdg, lacs2-3 and eca2, but not in wax mutants cer1-4 and cer3-6. Interestingly, these genes have recently been shown to be required to B. cinerea resistance. In contrast, we found the induction of genes involved in abiotic stress shared by the two wax mutants. Our study reveals new insights that the faster recognition of the pathogen by changes in the cuticular permeability is not enough to induce the resistance to B. cinerea as previously hypothesized. In addition, our data suggest that mutants with resistant phenotype can activate other defense pathways, different from those canonical immune ones.